Diversity, distribution and seasonal variation of seaweeds in Southwest coast of Peninsular India - Starlin, N. Maybel; Princy, S.; Samuel, P. David; Subitha, P.; Pepsi, A.; Sukumaran, S. (Current Botany, 2023)
Six different research locations around the southwest coasts of Tamil Nadu and Kerala were used for the current investigations on the diversity, distribution, and seasonal fluctuation of seaweeds (India). A total of 73 Chlorophyta, Ochrophyta and Rhodophyta were recorded under 23 families and 38 genera. The study site Rasthakaadu (53) was with the maximum number of seaweeds followed by Kanniyakumari (51). Out of six study sites, four study sites (Rasthakaadu, Kanniyakumari, Muttom, Kurumpanai) were dominant with Rhodophyta in contrast to the other two study sites (Vallavilai, Vizhinjam) in which Chlorophyta was dominant. Chlorophyta such as Chaetomorpha antannina, C. indica, C. media, Ulva fasciata, U. lactuca, brown seaweeds Sargassum ilicifolium and red seaweed Gracilariopsis longissima were commonly seen in the study area. Chaetomorpha indica (Chlorophyceae) was recorded as the most dominant species in season I, whereas Sargassum ilicifolium (Phaeophyaceae) was considered as the most dominant seaweed taxon in seasons II and III. The seasonal variation in physicochemical parameters of seawater had much influence on the growth of seaweeds. Comparing the eastern Coromandel Coast of peninsular India to the western Malabar Coast, it has been found from the current study that the eastern Coromandel Coast was rich in seaweed. Moreover, the study shows that the topography and seasonal change of the physicochemical characteristics of seawater at a given site were the key determinants of seaweed richness. Anthropogenic activities, like Nuclear power plants (Koodankulam), sand mining, construction works, dumping of plastics etc., also affected the potential growth of seaweeds thereby reducing the sustainability of the natural resource.